Quantifying variation in human scalp hair fiber shape and pigmentation. Issue 2 (9th March 2016) - Lasisi, Tina; Ito, Shosuke; Wakamatsu, Kazumasa; Shaw, Colin N.
ABSTRACT: Objectives: This study aims to evaluate the use of quantitative methods of measuring variation in scalp hair fiber shape and pigmentation and carry out exploratory data analysis on a limited sample of individuals from diverse populations in order to inform future avenues of research for the evolution of modern human hair variation. Methods: Cross‐sectional area and shape and average curvature of scalp hair fibers were quantified using ImageJ. Pigmentation was analyzed using chemical methods estimating total melanin content through spectrophotometric methods, and eumelanin and pheomelanin content through HLPC analysis of melanin‐specific degradation products. Results: The initial results reinforced findings from earlier, traditional studies. African and African Diaspora scalp hair was significantly curled, (East) Asian hair was significantly thick, and European hair was significantly lighter in color. However, pigmentation analyses revealed a high level of variability in the melanin content of non‐European populations and analysis of curvature found a large range of variation in the average curvature of East African individuals. Conclusions: Overall, these results suggest the usefulness of chemical methods for the elucidation of nonperceptible differences in scalp hair color and highlight the need for improvements in our assessment and understanding of hair fiber curvature. Am J Phys Anthropol 160:341–352, 2016. © 2016 Wiley Periodicals, Inc.